"The Project Changed My Life": Sport Education's Transformative Potential on Student Physical Literacy. Issue 2 (2nd April 2020) - Farias, Cláudio; Wallhead, Tristan; Mesquita, Isabel
ABSTRACT: Purpose : This longitudinal study provided a retrospective examination of the impact of student participation in a year-long Sport Education curricular experience on physical literacy development. A focus was placed on students' reported motivation, attitudes and disposition to participate in physical education (PE) and sport, and their re-actualizations of a healthy sport culture in the years following the Sport Education experience. Methods : Three years following the Sport Education experience, a cohort of 24 tenth-grade students (nine girls and 15 boys) were traced back and invited to share their recollected memories and accounts of their PE experience and subsequent attributes of physical literacy. The data collection protocol included augmented memory retrieval techniques and a retrospective survey, which informed semi-structured individual and focus groups interviews. A thematic analysis of data was performed and trustworthiness criteria included data triangulation, crosschecking, and collaborative interpretational analysis. Results : Prolonged participation in a year-long Sport Education curriculum promoted a transformation in students' physical literacy dispositions, both within and outside the school context. Physical literacy attributes included empathetic attitudes toward others, resilience against discriminatory learning activities and a commitment of the participants to actively pursue equitable and meaningful participation in PE and sport. Embodied interpersonal, managerial, and peer-teaching skills sustained the participants' sport culture activism against impoverished instructional practices in PE. Conclusions : Prolonged participation in Sport Education, and consequential development of enthusiasm, competency, and literacy can positively contribute to individuals' lifelong physical literacy journey.